2021
DOI: 10.1136/gpsych-2020-100254
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and Dandy-Walker syndrome: a case report and review of the literature

Abstract: Dandy-Walker syndrome (DWS) is a group of brain malformations which sometimes present with psychotic symptoms. We present the case of a patient diagnosed with Dandy-Walker variant who presented with schizophrenia-like psychosis. A man in his 30s was admitted to an acute psychiatric unit presenting with persecutory delusions, auditory hallucinations and violent behaviour. The MRI performed showed the typical alterations of Dandy-Walker variant: vermian hypoplasia and cystic dilatation of the fourth ventricle. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…We reviewed clinical and brain imaging data for 18 individuals from 15 reports (Bozkurt Zincir et al, 2014; Buonaguro et al, 2014; Dawra et al, 2017; Ferentinos et al, 2007; Gama, 2019; Gan et al, 2012; Kvitvik Aune & Bugge, 2014; Langarica & Peralta, 2005; Papazisis et al, 2007; Porras Segovia et al, 2021; Rohanachandra et al, 2016; Ryan et al, 2012; Trehout et al, 2019; Turner et al, 2001; Williams et al, 2016). The developmental and psychiatric data were often detailed, describing undifferentiated (unlabeled) psychosis in eight, SCZ in six, and SCZ‐like features in three individuals.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We reviewed clinical and brain imaging data for 18 individuals from 15 reports (Bozkurt Zincir et al, 2014; Buonaguro et al, 2014; Dawra et al, 2017; Ferentinos et al, 2007; Gama, 2019; Gan et al, 2012; Kvitvik Aune & Bugge, 2014; Langarica & Peralta, 2005; Papazisis et al, 2007; Porras Segovia et al, 2021; Rohanachandra et al, 2016; Ryan et al, 2012; Trehout et al, 2019; Turner et al, 2001; Williams et al, 2016). The developmental and psychiatric data were often detailed, describing undifferentiated (unlabeled) psychosis in eight, SCZ in six, and SCZ‐like features in three individuals.…”
Section: Resultsmentioning
confidence: 99%
“…We performed a literature review using pairs of search terms with the first search term either “psychosis” or “schizophrenia,” and the second search term “cerebellar hypoplasia,” “Dandy–Walker malformation” or “Dandy–Walker variant.” Our search yielded 17 papers from 2007 to 2021 describing 20 individuals. Three papers were discarded due to inadequate or no brain imaging, leaving 17 reported individuals plus our proband (Bozkurt Zincir et al, 2014; Buonaguro et al, 2014; Dawra et al, 2017; Ferentinos et al, 2007; Gama, 2019; Gan et al, 2012; Kvitvik Aune & Bugge, 2014; Langarica & Peralta, 2005; Papazisis et al, 2007; Porras Segovia et al, 2021; Rohanachandra et al, 2016; Ryan et al, 2012; Trehout et al, 2019; Turner et al, 2001; Williams et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia-like symptoms induced by neurological lesions may present clinical features that differentiate them from primary schizophrenia, which may result in the need for different treatment approaches. [ 13 ] The case may further illuminate the physio-pathology and treatment strategy of psychotic disorders with congenital cerebellum malformation.…”
Section: Introductionmentioning
confidence: 99%
“…Reviewing the literature, the authors have found a few published cases describing co-occurrence of psychotic symptoms and DWS. [2,5,[13][14][15][16] However, few report has described the patient with DWM and hydrocephalus after undergoing surgery. In the present study, we describe a case of a young man who was diagnosed with DWM and seizure co-morbid with suspected atypical schizophrenia-like symptoms.…”
Section: Introductionmentioning
confidence: 99%